IL‐6 signaling in acute exercise and chronic training: Potential consequences for health and athletic performance. (8th October 2022) - Nash, Dan; Hughes, Michael G.; Butcher, Lee; Aicheler, Rebecca; Smith, Paul; Cullen, Tom; Webb, Richard
Abstract : The cytokine interleukin‐6 (IL‐6) is involved in a diverse set of physiological processes. Traditionally, IL‐6 has been thought of in terms of its inflammatory actions during the acute phase response and in chronic conditions such as rheumatoid arthritis and obesity. However, IL‐6 is also an important signaling molecule during exercise, being acutely released from working muscle fibers with increased exercise duration, intensity, and muscle glycogen depletion. In this context, IL‐6 enables muscle‐organ crosstalk, facilitating a coordinated response to help maintain muscle energy homeostasis, while also having anti‐inflammatory actions. The range of actions of IL‐6 can be explained by its dichotomous signaling pathways. Classical signaling involves IL‐6 binding to a cell‐surface receptor (mbIL‐6R; present on only a small number of cell types) and is the predominant signaling mechanism during exercise. Trans‐signaling involves IL‐6 binding to a soluble version of its receptor (sIL‐6R), with the resulting complex having a much greater half‐life and the ability to signal in all cell types. Trans‐signaling drives the inflammatory actions of IL‐6 and is the predominant pathway in disease. A single nucleotide polymorphism (rs2228145) on the IL‐6R gene can modify the classical/trans‐signaling balance through increasing the levels of sIL‐6R. This SNP has clinical significance, having been linked to inflammatory conditions such as rheumatoid arthritis and type 1 diabetes, as well as to the severity of symptoms experienced with COVID‐19. This review will describe how acute exercise, chronic training and the rs2228145 SNP can modify the IL‐6 signaling pathway and the consequent implications for health and athletic performance.